“Cais@law” accounting information system for small law firms in Malaysia - Wan Nur Syahida, Wan Ismail; Zuhairah Ariff, Abd Ghadas; Fatimah, Ghazali (2016)
ln Malaysia, as of January 2016, nearly 90% of the legal firms comprise of less than five partners (4,818 firm out of 5,405 firms registered). With small number of partners and lack io knowledge in accounting, it is perceived that a special accounting management system for the Jaw Finns would be very useful for the lawyers to operate their accounts and book keeping. At present, there are many software on legal firms account management system, for example, the MyCase's web based legal practice management software and the QuickBooks legal accounting software. However, most of these international formulated software are expensive and might not be suitable to cater the practice of local small Jaw firms.